2019
DOI: 10.1038/s41598-018-38358-w
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Bisphenol-A using N, Co Codoped TiO2 Catalyst under Solar Light

Abstract: Advanced oxidation processes (AOPs) including heterogeneous photocatalysis has proven as one of the best technique for waste-water treatment. Photocatalytic process using semiconductor like TiO2 based heterogeneous photocatalysis is a promising method for the treatment of toxic pollutants. In the present study, visible-light photoactive cobalt and nitrogen co-doped TiO2 nanoparticles were synthesized via wet impregnation method. The photocatalysts were characterized using X-ray diffraction (XRD), Raman Spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(45 citation statements)
references
References 39 publications
3
42
0
Order By: Relevance
“…This is the first attempt to integrate MD with a thermocatalyst and the new technology still presents some challenges. Firstly, despite the kinetic constants for BPA degradation for CSF under dark conditions have the same magnitude of those observed for the traditional TiO 2 photocatalysts under UV light [48][49][50][51] , our perovskite contains cerium, which makes it intrinsically more expensive than TiO 2 . Moreover, the perovskite was synthetized by the solutioncombustion method, which is a well-established and reproducible lab-scale procedure.…”
Section: Discussionmentioning
confidence: 79%
“…This is the first attempt to integrate MD with a thermocatalyst and the new technology still presents some challenges. Firstly, despite the kinetic constants for BPA degradation for CSF under dark conditions have the same magnitude of those observed for the traditional TiO 2 photocatalysts under UV light [48][49][50][51] , our perovskite contains cerium, which makes it intrinsically more expensive than TiO 2 . Moreover, the perovskite was synthetized by the solutioncombustion method, which is a well-established and reproducible lab-scale procedure.…”
Section: Discussionmentioning
confidence: 79%
“…Nowadays, photocatalysts gain particular interest as they enable conversion of, for example, solar into chemical energy, allowing chemical reactions to occur. A very important branch of photo-driven catalytic reactions is those using nanoparticles (NPs) as a controlling factor in processes such as wastewater treatment [3,4], CO 2 reduction [5,6], or hydrogen generation [7,8].Hybrid nanosystems, such as ZnO nanoparticles with Au domains [9,10], Au tipped CdSe nanorods [11], Pt-decorated CdS nanorods [12], CdSe nanoplatelets with Pd domains [13], Cu 2 O NPs with Au core [14], and even more complex systems like TiO 2 nanowires enriched with Au NPs and deposited Cu 7 S 4 [15], have been recently proposed as photocatalysts and solar energy converters. A very interesting approach was proposed by Yu et al [16], who synthesized Ag/AgCl/TiO 2 nanotube arrays and demonstrated their photocatalytic activity, taking visible light-driven methyl orange degradation as an example.…”
mentioning
confidence: 99%
“…Nowadays, photocatalysts gain particular interest as they enable conversion of, for example, solar into chemical energy, allowing chemical reactions to occur. A very important branch of photo-driven catalytic reactions is those using nanoparticles (NPs) as a controlling factor in processes such as wastewater treatment [3,4], CO 2 reduction [5,6], or hydrogen generation [7,8].…”
mentioning
confidence: 99%
“…Therefore, metal and non-metal ion co-doping enhance photocatalytic activity [163,171]. Garg et al [172] tested the photocatalytic performance of prepared N and Co-co-doped TiO 2 on the removal of Bisphenol-A under visible light. The results showed that the maximum degradation rate (95%) was observed when using 1.5% Co and 0.5% N co-doping TiO 2 .…”
Section: Different Elements Co-doping Tiomentioning
confidence: 99%